INTERCONNECTIONS AND COMPLEMENTARITY OF MOTOR-MECHANIC AND MOTOR-PARTS BUSINESS IN ROAD TRANSPORTATION IN SOUTHEAST NIGERIA, 1906 – 2020 - Uzoma Samuel Osuala (Romanian Journal of Historical Studies)
Motor-parts business emerged in response to advent of road construction. The early roads and bridges constructed in colonial Nigeria had negative impacts on most vehicles. This was further compounded by the routine wear and tear associated with mechanical automobiles and the low technical know-how among the early motorists. Hence, automobiles incessantly broke down which obviously impeded the business of both private and commercial motor transporters. This challenge, however, was ameliorated with the availability of motor parts and motor-mechanics. In fact, availability of motor-parts was insufficient and worthless without motor mechanics to fix them. In other words, motor-parts and motor-mechanics are inseparable in road transportation. So, effective functionality of vehicular transportation is dependent on the synergy and complementarity of motor-mechanics and availability auto-parts. This narrative is obviously absent in Nigerian transport history literature. It is the aim of this discourse to give voice to these interconnections, particularly to the silent motor mechanics whose significant contributions to road transportation and motor-parts business have remained unnoticed. The methodology is historical and expository narrative. Texts and data collected from primary and secondary sources are chronologically and thematically presented.